POTENTIAL MAPPING OF PESANTREN AS COMMUNITY ECONOMIC EMPOWERMENT CAPITAL - Cahayu Arum Min Tasnim; Eni Wuryani (Journal of Economics, Business, and Government Challenges, 2021)
This study aims to examine the effect of the Investment Opportunity Set (IOS) and Firm Size on Firm Value. This research was conducted at companies listed on the Jakarta Islamic Index for the period 2017-2020. The sample used in this study were 116 companies listed in the Jakarta Islamic Index for the 2017-2020 period. The sampling technique used was purposive sampling. The type of data used in this study is secondary data obtained from www.idx.co.id. The data analysis technique used is multiple linear regression. The dependent variable in this study is firm value while the independent variables are Investment Opportunity Set (IOS) and Firm Size . Based on the analysis results show the Investment Opportunity Set (IOS) has a positive and significant effect on firm value, and firm size has no effect on firm value.